Switching to Bortezomib may Improve Recovery From Severe Vincristine Neuropathy in Pediatric Acute Lymphoblastic Leukemia - Joshi, Jaitri; Tanner, Lynn; Gilchrist, Laura; Bostrom, Bruce (Journal of pediatric hematology/oncology, 2019)
The purpose of this study was to evaluate the impact of switching patients being treated for acute lymphoblastic leukemia (ALL) from vincristine to bortezomib. A total of 20 patients with ALL were switched from vincristine to bortezomib (1.3 mg/m/dose) because of worsening neuropathy despite physical therapy interventions (n=18) or at increased risk of neuropathy (n=2). Relapse rates were compared with 56 vincristine-only patients matched by prognostic factors. Maintenance blood counts in bortezomib patients were compared with cooperative group data using vincristine during maintenance. In addition, 6 evaluable patients were assessed for neuropathy using the pediatric-modified total neuropathy score. Neuropathy scores were collected during treatment with vincristine and after switching to bortezomib. After a median follow-up of 3.5 years the relapse rate in patients switched to bortezomib was nonsignificantly different than those remaining on vincristine. Patients on monthly bortezomib had statistically significantly lower platelet counts that did not require transfusions or dose adjustment. Total neuropathy for all 6 cases decreased significantly when switched to bortezomib from vincristine (P=0.015), with motor neuropathy declines in 5 of 6 subjects. Bortezomib substitution for vincristine in ALL treatment is a potential strategy to mitigate severe vincristine neuropathy. These findings should be confirmed in a randomized clinical trial to further assess benefits and risks of this approach.